Generation Y attitudes and perceptions on career and job-hopping culture in Singapore : facing the stigma and how they behave. - Sim, Joshua Wei Rong (2017)
This study seeks to understand how Generation Y workers, shaped by different environment, view career attitudes, perceive job-hopping and the influence of stigmatisation of job-hoppers on their career decision and choices. The research gap shows the lack of updated and relevant studies especially on job-hopping attitudes and behaviours of Generation Y workers, as well as the lack of studies on the extent and effect of stigmatisation of job-hopping and how it is managed. 16 Generation Y working adults were interviewed, revealing that the top motivational factors are seeking learning opportunities at work, career progression opportunities and the need for a team environment. In summary, results show that Generation Y workers in Singapore view job-hopping to be generally beneficial and positive, that there is a relatively low stigma towards job-hopping among Generation Y workers and where Gen Y working adults are mostly accepting of job-hopping behaviours.